A dialogue with the past and a future projection: history, verismo and dystopia in Hunger Games - Valdinei José Arboleya (Travessias, 2016)
Juvenile literature is recurrently identified as gender connected to the reader in training and the references to the wonderful universe and the utopia. These characteristics are unquestionable, however, this genre is an art form that can be opened to other forms of representation and aesthetic proposition that allow different ways of recreation of reality. Based on this argument, the objective of this study is to analyze the Hunger Games trilogy, written by Suzanne Collins, from the perspective of dystopia and the concept of new verismo, or new realism, from Italian vero, that means "true". These categories of analysis are present throughout the trilogy, forming the basis on which develops narration, which presents a complex reality projected into the future, however, with past echoes. This analysis seeks to observe how are articulated some dystopia elements in the narrative and how the text projects a dialogue, sometimes meticulous, with aspects from ancient history and contemporary social and cultural relations.